Lire ou écrire, il ne faut pas choisir. L’écrivain et la lecture en public - Arnaud Rykner (Itinéraires)
Reading in public is an experience of shared reading or even of collective reading. In the body of the person reading, as much as through his voice and his imagination, a multitude of I’s converge—I’s that are Others—including and especially when the reader is also the writer. Read and write are then shown to be the two sides of a same creative and participative gesture that makes possible the exploration and confrontation of the otherness inside us all.